"I actually got my first job through my ex-colleague": Employment-related information seeking behavior of Bangladeshi immigrants in Canada. (March 2022) - Shuva, Nafiz Zaman
This study explores the employment-related information seeking behaviour of Bangladeshi immigrants in Canada. Using a mixed-methods approach, the study conducted semi-structured interviews with 60 Bangladeshi immigrants in Ontario, Canada, and obtained 205 survey responses. The study highlights the centrality of employment-related settlement among Bangladeshi immigrants in Ontario and reports many immigrants not being able to utilize their education and skills after arrival in Canada. The results show that Bangladeshi immigrants utilize various information sources for their employment in Canada, including friends and professional colleagues, online searchers, and settlement agencies. Although Bangladeshi immigrants utilized a large array of information sources for meeting their employment-related information needs, many interview participants emphasized that the employment-related benefits they received was because of their access to friends and professional colleagues in Canada. The survey results echoed the interview findings. The cross-tabulation results on post-arrival information sources and occupation status as well as first job information sources and occupational status in Canada show a significant association among the use of the information source "friends and professional colleagues in Canada" and immigrants' occupational status. The study highlights the benefits of professional colleagues among immigrants in employment-related settlement contexts. It also reports the challenges faced by many immigrant professionals related to employment-related settlement because of the lack of access to their professional friends and colleagues in Canada. The author urges the Federal Government of Canada, provincial governments, and settlement agencies working with newcomers to offer services that would connect highly skilled immigrants with their professional networks in Canada, in order to get proper guidance related to obtaining a professional job or alternative career. The author calls for further studies on employment-related information seeking by immigrants to better understand the role information plays in their settlement in a new country.